Effects of carbohydrate refeeding on physiological responses and psychological and physical performance following acute weight reduction in collegiate wrestlers - Finn, K. J.; Dolgener, F. A.; Williams, R. B. (The Journal of Strength and Conditioning Research, 2004)
The purpose of this study was to determine the effects of carbohydrate refeeding on intermittent sprint exercise, blood lactate response, and mood following a typical weight-reduction program practiced by college wrestlers. Fifteen collegiate wrestlers from the University of Northern Iowa completed 3 trials of intermittent arm cranking and a mood inventory prior to weigh-ins (baseline), after weigh-ins, and 1 hour postconsumption of either 1.5 g carbohydrate (CHO)/kg body mass carbohydrate beverage (25% solution) or placebo taken within 1 hour after weigh-ins. Blood lactate responses were determined with each trial. Repeated measures analysis of variance indicated no significant interaction between group and trial for total work (p = 0.08), blood lactate (p = 0.29), positive mood (p = 0.49), or negative mood (p = 0.78). Simple effects analysis indicated a significant difference in lactate response between trials (p = 0.002); however, no difference for work (p = 0.75), positive mood (p = 0.13), or negative mood (p = 0.08). The results of this study suggest that intermittent sprint exercise, blood lactate response, and mood were not positively affected by ingestion of CHOs following an acute weight-reduction period